2019
DOI: 10.1186/s13578-019-0300-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SNPs interplay across the locus of MBL2, between MBL and Dectin-1 gene, on women’s risk of developing recurrent vulvovaginal infections

Abstract: Background Human mannose binding lectin (MBL) and dendritic cell-associated C-type lectin-1 (Dectin-1) are the two prototypical PRRs of innate immunity, whose direct role in recurrent vulvovaginal infections (RVVI) defense has been defined. Previously, MBL insufficiency was proposed as a possible risk factor for the rapid progression of RVVI while, Dectin-1 was found to be playing an active role in the defense. However, the complete genetic bases for the observed low MBL levels are still lacking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We investigated the associations of previously reported SNPs in relation to BV or vaginal microflora to determine whether these associations are relevant in a Kenyan population ( 19 26 ). Figure 3 and Table S3 summarize these findings.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the associations of previously reported SNPs in relation to BV or vaginal microflora to determine whether these associations are relevant in a Kenyan population ( 19 26 ). Figure 3 and Table S3 summarize these findings.…”
Section: Resultsmentioning
confidence: 99%
“…Human mannose-binding lectin (MBL) and dendritic cell-associated C-type lectin-1 (Dectin-1) are the two prototypical PRRs of innate immunity, whose direct role in defense against RVVI pathogens has been defined (Ip & Lau, 2004;Pellis et al, 2005;Ferwerda et al, 2009;Li et al, 2012b). Moreover, our studies along with others have suggested the involvement of these PRRs in determining RVVI susceptibility (Ferwerda et al, 2009;Babula et al, 2003;Liu et al, 2006;Milanese et al, 2008;Henić et al, 2010;Ghazanfari et al, 2017;Kalia et al, 2017Kalia et al, , 2018Kalia et al, , 2019aKalia et al, , 2019b. In addition, both MBL and Dectin-1 have been shown to mediate ROS release as a part of defense mechanism against pathogens (Li et al, 2012b;Underhill et al, 2005;Kalia et al, 2016;Lima-Junior et al, 2017).…”
Section: Introductionmentioning
confidence: 62%
“…Several SNPs in the MBL2 region were significantly associated with L. iners, G. vaginalis, and CST. Kalia et al studied these previously reported MBL2 SNPs in association with BV in women in India due to associations between mannose binding lectin (MBL) insufficiency and increased susceptibility to infectious diseases [30]. Among Brazilian women, a specific MBL2 polymorphism was associated with increased odds of recurrent BV compared to controls [31], though a study among Italian women that screened for three specific MBL2 SNPs found no differences for women with recurrent BV as compared to controls [32].…”
Section: Discussionmentioning
confidence: 99%